Oral health condition of the Brazilian adolescents and its influence on dental diversity patterns for human identification - Deitos, Alexandre Raphael; Azevedo, Alana de Cássia Silva; Michel-Crosato, Edgard; Biazevic, Maria Gabriela Haye (South European Journal of Orthodontics and Dentofacial Research (SEJODR), 2017)
Introduction: Forensic dentistry makes possible the identification of a great number of individuals. The combination of the anatomic alvariability of the teeth with the several types of dental treatment creates numerous dental patterns.Aim: The aim of the study was to verify if the improvement in the oral health condition of the Brazilian adolescents would interferein the analysis of the dental diversity patterns and its potential use for human identification in forensic sciences.Materials and methods: The use of the clinical dental condition records, available in the database from the last two Brazilian National Oral Health Surveys (2003-2010), enabled the assessment of dental patterns.Results: The national and regional conditional diversity values calculated for complete and partial dentition (common situation in amass disaster event) - 0.911 to 0.997, P > 0.05 are similar to the diversity patterns values of mitochondrial DNA.Conclusion: The improvement in the oral health condition of Brazilian adolescents did not interfere with the potential use of dentaldiversity patterns as an objective method of human identification. However, it is necessary to develop other methodologies topotentiate the use of forensic dentistry, since oral health conditions change over time.